Biosorption Cr(VI) using Biofilm Streamer - Andi Kurniawan (Jurnal Perikanan Universitas Gadjah Mada, 2019)
Water contamination is one of the main environmental problem presently. One of the contaminants that become serious problem in aquatic ecosystems is Cr(VI) which is toxic for living organisms. Therefore, technology to solve this problem is urgent. Biosorption is one of the alternative technologies that inexpensive and environmentally friendly. The present study analyzed the biosorption of Cr(VI) using streamer biofilm. Biofilm is a predominant habitat for most microbes in aquatic ecosystems. The sample of biofilms used in this study was streamer biofilm collected from the river. The results show that the streamer biofilm had ability to adsorb Cr(VI). The adsorption of Cr(VI) are fitted well to the Langmuir adsorption isotherm model. The maximum adsorbed amount of Cr(VI) is estimated to be around 8.33 mg/g and the adsorption equilibrium constant is around 0.02 L/mg. The results of the present study indicate that the streamer biofilm is a promising alternative biosorbent for the biosorption of water pollutant such as Cr(VI).